cAMP-specific phosphodiesterase 8A and 8B isoforms are differentially expressed in human testis and Leydig cell tumor - Campolo, Federica; Capponi, Chiara; Tarsitano, Maria Grazia; Tenuta, Marta; Pozza, Carlotta; Gianfrilli, Daniele; Magliocca, Fabio; Venneri, Mary A.; Vicini, Elena; Lenzi, Andrea; Isidori, Andrea M.; Barbagallo, Federica (Frontiers in Endocrinology, 2022)
Cyclic adenosine monophosphate/Protein kinase A (cAMP/PKA) signaling pathway is the master regulator of endocrine tissue function. The level, compartmentalization and amplitude of cAMP response are finely regulated by phosphodiesterases (PDEs). PDE8 is responsible of cAMP hydrolysis and its expression has been characterized in all steroidogenic cell types in rodents including adrenal and Leydig cells in rodents however scarce data are currently available in humans. Here we demonstrate that human Leydig cells express both PDE8A and PDE8B isoforms. Interestingly, we found that the expression of PDE8B but not of PDE8A is increased in transformed Leydig cells (Leydig cell tumors-LCTs) compared to non-tumoral cells. Immunofluorescence analyses further reveals that PDE8A is also highly expressed in specific spermatogenic stages. While the protein is not detected in spermatogonia it accumulates nearby the forming acrosome, in the trans-Golgi apparatus of spermatocytes and spermatids and it follows the fate of this organelle in the later stages translocating to the caudal part of the cell. Taken together our findings suggest that 1) a specific pool(s) of cAMP is/are regulated by PDE8A during spermiogenesis pointing out a possible new role of this PDE8 isoform in key events governing the differentiation and maturation of human sperm and 2) PDE8B can be involved in Leydig cell transformation.